The Effect of 6-gingerol on Growth Factors and Apoptosis Indices in Rats Exposed to Gold Nanoparticles - Ghasem Majdi Yazdi; Gholamhasan Vaezi; Vida Hojati; Mohammad Mohammad-Zadeh (Basic and Clinical Neuroscience, 2021)
Introduction: Research has shown that gold nanoparticles (AuNPs) can damage the physiological processes of brain tissue. Given the antioxidant properties of Gingerol (GING), this study aimed to determine the protective effect of 6-gingerol on hippocampal levels of Brain-Derived Neurotrophic Factor (BDNF), Nerve Growth Factor (NGF), DNA oxidative damage, and the amount of Bax and Bcl2 apoptosis indices of rats exposed to AuNPs. Methods: A total of 42 male Wistar rats were divided into four groups: control (30 days 0.5 mL saline), AuNPs (one time injection of 0.5 mL AuNPs, 200 ppm and 60 Nm + 30 days 0.5 mL saline), AuNPs+GING 50 (one time injection of 0.5 mL AuNPs, 200 ppm and 60 Nm + 30 days 0.5 mL density of gingerol 50 mg/kg), and AuNPs+GING100 (one time injection of 0.5 mL AuNPs, 200 ppm and 60 Nm + 30 days 0.5 mL density of gingerol 100 mg/kg). At the end of the treatment period, the hippocampal levels of NGF, BDNF, 8-hydroxy-desoxyguanosine (8-HOdG), and apoptotic indices of Bax and Bcl-2 were assessed with the ELISA method. Results: Compared with the AuNPs group, hippocampal levels of BDNF, NGF, and Bcl-2 in rats in the AuNPs+GING 50 and AuNPs+GING 100 groups significantly increased dose-dependently. However, the hippocampal levels of Bax and 8-HOdG significantly decreased dose-dependently (P<0.05). Conclusion: According to obtained results, gingerol may improve hippocampal BDNF and NGF levels in rats exposed to AuNPs, probably by reducing apoptosis and oxidative DNA damage.